Structural, electronic, magnetic and optical properties of Zn-Ni-Co ternary spinel oxide based Co₃O₄ by using density functional theory with hubbard U (DFT+U) for supercapacitors electrode / Nur Hamizah Mohd Zaki - Mohd Zaki, Nur Hamizah (2022)
Cobalt oxide, Co3O4 is a magnetic semiconductor containing cobalt ions, Co2+ and Co3+ at tetrahedral and octahedral sites respectively. It is considered a good electrode material for supercapacitors due to possessing of redox reversible behaviour. Unfortunately, Co3O4 is suffering from inferior ion transport kinetics and poor electrical conductivity, which can affect the rate capability and cycling stability of the electrodes. Modifying the spinel Co3O4 via doping with other 3d transition metals could offer a rich redox reaction, hence can improve the performance of the electrode. This thesis presents the theoretical work for zinc-nickel-cobalt (Zn-Ni-Co) ternary oxide from metal (M)- doped Co3O4 (M=Ni, Zn) by using density functional theory (DFT) that has been implemented in Cambridge Serial Total Energy Package (CASTEP) software code to calculate the structural, electronic, magnetic and optical properties. It is started with the cubic spinel Co3O4 where the findings on structural parameters show Co3O4 is calculated to be in antiferromagnetic (AFM) with cation (Co2+) magnetic moment of 2.37μ. The band gap of Co3O4 obtained (0.11eV) is severely underestimated with respect to the experimental value. Thus, the inclusion of the Hubbard U (DFT+U) method can give a better description of the cobalt localized d states. From optical properties, it is predicted that the electron transition occurs between p-d and d-d orbital. The second part involves is Ni-doped Co3O4 (NiCo2O4) and Zn-doped Co3O4 (ZnCo2O4) to form binary metal oxide. Due to spinel structure exhibiting two sites, the cation distribution namely x=0 (normal spinel) and x=1 (inverse spinel) of doped metal among tetrahedral and octahedral must be considered first. It is important due to the cation distribution greatly influences the properties of the material, especially the electronic properties. The findings show the NiCo2O4 is energetically favourable in inverse spinel meanwhile ZnCo2O4 is a normal spinel structure. From band gap and density of states analysis, NiCo2O4 has transformed from semiconductor to half-metallic behaviour meanwhile ZnCo2O4 remains as a semiconductor. Among these two metal-doped, the NiCo2O4 are greatly improved the electrical conductivity due to the occurrence of the exchange interaction between Ni 3d states with Co 3d states. To form the ternary oxide, the co doped Zn into NiCo2O4 with different doping ratios (x=0.25,0.50 and 0.75) were calculated. The introduction of Zn has provoked atomic bonding and structure. From the density of states analysis, the value near the Fermi level at higher doping ratio x=0.75, namely Ni1.0Zn0.75Co1.25O4 (16.13electron/eV) has increased from binary oxide, NiCo2O4 (12.30electron/eV). Such an increase of this value leads to enhancement the electrical conductivity. It can reasonably explain its low resistance consequently enhancing the supercapacitive performances. Overall, the first-principles study in this work from the deepest level of atomic-scale scope can describe the properties of materials and may improve the understanding of supercapacitors.